Pengaruh Penerapan Fungsi – Fungsi Manajemen terhadap Kreativitas Kerja Pegawai: Pada Kantor Dinas Pemuda Olahraga dan Pariwisata Kabupaten Wajo - Burhanuddin Burhanuddin; Muktamir Usman; Supris Musiafir; Ekayani Burhanuddin (BADAN PENERBIT STIEPARI PRESS, 2025)
Employees at the Wajo Regency Youth, Sports and Tourism Office are one of the public bureaucracies at the Regency/City level carrying out service functions to the community, according to the results of initial observations show that the implementation of management functions and employee work creativity is still not optimal, especially related to the implementation of management functions in terms of implementation (creating a dynamic work atmosphere/making the best use of time). This research was conducted to determine the effect of the application of management functions on the work creativity of employees at the Wajo Regency Youth, Sports and Tourism Office. The research population is all employees at the Wajo Regency Youth, Sports and Tourism Office using a survey research type with a quantitative associative approach.The results of this study show that the variables of management functions, based on respondents' responses are at the very good criteria, and the work creativity variables are at the good criteria. Based on the results of statistical testing, Ho was rejected and Ha was accepted, so it was concluded that the implementation of management functions had a positive and significant effect on the work creativity of employees at the Wajo Regency Youth, Sports and Tourism Office.